Let $(\theta,A\theta)=\theta_i A_{ij}\theta_j$ where $A$ is some $(2\times2)$ antisymmetric matrix.

I want to generalize the following

$$I(A) =\int d\theta_1d\theta_2~ \exp\Bigg[\frac{1}{2}(\theta,A\theta)\Bigg]=\int d\theta_1d\theta_2~ (1+\theta_1\theta_2A_{12}) = A_{12}=\sqrt{\det A}$$

to the $n$-tuple case.

Let now $$A:=\begin{bmatrix} 0 & 1 & \; & \; \\ \;-1 & 0 & & \; \\ \; & \; & 0 & 1 \\ \; & \; & -1 & 0 \\ \; & \; & \; & \, &\ddots \\ \end{bmatrix}.$$

I evaluate, I get the following $$I(A) = \int d\theta_n\dots d\theta_1\,\exp\Bigg[\frac{1}{2}(\theta,A\theta)\Bigg]\\ = \int d\theta_n\dots d\theta_1\, (\theta_1\theta_2+\theta_3\theta_4+\cdots)\\=0$$

The answer should be $$I(A) = 1.$$

In the above I use (perhaps incorrectly?)

$$\int d\theta_n\dots d\theta_1\, \theta_n\dots \theta_1\, = 1 $$ and $$\int d\theta_n\dots d\theta_1= 0. $$

Where do I err?

EDIT: I think I know how to fix this: it is the last term in the expansion of the exponential the contributes. All other terms give zero (just like the one above). I will add the solution later.


The problem is that you are generalizing the real Gaussian integral to the Grassmannian case rather than the complex Gaussian integral $\int dz d\bar{z} e^{-(z, Az)}$, where $(z, A z) = \sum_{i,j} z_i A_{ij} \bar{z}_j$ and $d z d\bar{z} = dz_1 d\bar{z}_1 \ldots dz_n d\bar{z}_n$.

You can see that the determinant will not arise by looking at the $2$-dimensional case. That is, let $A$ be a $2 \times 2$ matrix with entries $A_{ij}$. Then $(\theta, A \theta) = \theta_1 A_{12} \theta_2 + \theta_2 A_{21} \theta_1$. The anti-commutativity kills the $A_{11}$ and $A_{22}$ that you need in the determinant of $A$.

To fix this, introduce "conjugate variables" $\bar{\theta}_1$ and $\bar{\theta}_2$. The bar doesn't denote any kind of operation on the $\theta_i$. The $\bar{\theta}_i$ are just new Grassmann variables. Then define \begin{equation} (\theta, A \bar{\theta}) = \theta_1 A_{11} \bar{\theta_1} + \theta_1 A_{12} \bar{\theta}_2 + \theta_2 A_{21} \bar{\theta}_1 + \theta_2 A_{22} \bar{\theta}_2. \end{equation} The terms $\theta_i A_{ii} \bar{\theta}_i$ no longer vanish because there are no relations between $\theta_i$ and $\bar{\theta}_i$. Now \begin{equation} \int d\theta_1 d\bar{\theta}_1 d \theta_2 d\bar{\theta}_2 e^{-(\theta, A \bar{\theta})} = \int d\theta_1 d\bar{\theta}_1 d \theta_2 d\bar{\theta}_2 \frac{1}{2} (\theta, A \bar{\theta})^2 \end{equation} since the first two terms $1$ and $-(\theta, A \bar{\theta})$ in the exponential vanish under integration and the higher-order terms $(\theta, A \bar{\theta})^n$ for $n \geq 3$ vanish by anti-commutativity.

Now a computation shows that $(\theta, A \bar{\theta})^2 = 2 \theta_1 \bar{\theta}_1 \theta_2 \bar{\theta}_2 \det A$, so \begin{equation} \int d\theta_1 d\bar{\theta}_1 d \theta_2 d\bar{\theta}_2 e^{-(\theta, A \bar{\theta})} = \det A. \end{equation}

Given Grassmann variables $\theta_i, \bar{\theta}_i$ for $i = 1, \ldots, n$, defining $(\theta, A \bar{\theta}) = \sum_{i,j=1}^n \theta_i A_{ij} \bar{\theta}_j$ yields $\int d\theta_1 d\bar{\theta}_1 \ldots d\theta_n d\bar{\theta}_n e^{-(\theta, A \bar{\theta})} = \det A$ by a similar computation (this is really an exercise in bookkeeping).


You are absolutely right in your edit. Only the highest order term of the expansion survives integration. This is because $\int d\theta_i=0$ so that we need a term where all grassmann variables are there ($\int d\theta_n...d\theta_1 \theta_1...\theta_n=1$).

I noticed that this post is really old but still felt like replying as this connects to subjects maters I am currently studying about majorana fermions in physics.

In general one can always write a "gaussian" integral over real grassmann variables as \begin{equation} \int d\theta_1d\theta_2...d\theta_N \exp\left\{-\frac{1}{2}\sum_{i,j=1}^N\theta_iA_{ij}\theta\right\}. \end{equation} Where $A$ is a $N\times N$ real skew-symmetric matrix. Now notice that such matrices have the following properties:

Assume $\vec{x}$ to be an eigenvector of $A$ than $A\vec{x}=\lambda\vec{x}$ and $(A\vec{x})^\dagger=(\lambda\vec{x})^\dagger \rightarrow \vec{x}^\dagger A^T=\lambda^*\vec{x}^\dagger$ using this

\begin{equation} \label{Im} \begin{split} \vec{x}^\dagger A^T\vec{x}&=\lambda^*\vec{x}^\dagger\vec{x}\\ \vec{x}^\dagger (-A)\vec{x}&=\lambda^*\vec{x}^\dagger\vec{x}\\ -\lambda\vec{x}^\dagger\vec{x}&=\lambda^*\vec{x}^\dagger\vec{x}\\ -\lambda&=\lambda^* \end{split} \end{equation}

so that

\begin{equation} \label{pairs} \begin{split} (A\vec{x})^*&=(\lambda\vec{x})^*\\ A\vec{x}^*&=\lambda^*\vec{x}^*\\ A\vec{x}^*&=-\lambda\vec{x}^*. \end{split} \end{equation}

We have found that $\lambda_i$ is pure imaginary and that all eigenvalues appear in $\pm\lambda$ pairs. Consequently $A$ has the following spectrum of eigenvalues

\begin{equation} \label{spec} \lambda(A)=\{\pm i\lambda_1, \pm i\lambda_2,...,\pm i\lambda_m\}\quad\quad\text{Where}\quad\lambda_i\in\mathbb{R} \end{equation}

As a side note observe that if $N$ is uneven that at least one of the eigenvalues must be zero. This is not the case for even $N$ where we have defined $(N=2m)$. Using the property that the determinant is so called similarity invariant (similar matrices give the same determinant) we can write

\begin{equation} \label{det} \det(A)=\prod_{i=1}^m\lambda_i^2 \end{equation}

Also note that such a matrix can be put in to block-diagonal form by special-orthogonal transformation $D=OAO^T$ (see wiki) to get \begin{equation} \begin{split} D&=diag\left(\left( \begin{matrix} 0 & \lambda_1 \\ -\lambda_1 & 0 \end{matrix} \right) , \left( \begin{matrix} 0 & \lambda_2 \\ -\lambda_2 & 0 \end{matrix} \right) ,..., \left( \begin{matrix} 0 & \lambda_m \\ -\lambda_m & 0 \end{matrix} \right)\right) \end{split} \end{equation}

We can now start looking at the integral. First lets show that the measure will be invariant under change of variables $O_{ij}\psi_j=\psi_i'$ since

\begin{equation} \begin{split} \prod_i^N\theta_i'&=\frac{1}{N!}\epsilon_{i_1,i_2,...,i_N}\theta_{i_1}'\theta_{i_2}'...\theta_{i_N}'\\ &=\frac{1}{N!}\epsilon_{i_1,i_2,...,i_N}O_{i_1,i_1'}\theta_{i_1'}O_{i_2,i_2'}\theta_{i_2'}...O_{i_N,i_N'}\theta_{i_N'}\\ &=\frac{1}{N!}\epsilon_{i_1,i_2,...,i_N}U_{i_1,i_1'}O_{i_2,i_2'}...O_{i_N,i_N'}\epsilon_{i_1',i_2',...,i_N'}\prod_i^N\theta_{i}\\ &=\det(O)\prod_i^N\theta_{i}\\ &=\prod_i^N\theta_{i} \end{split} \end{equation}

This means that (omitting the apostrophe's) we can write the integral in the following form and start to solve it

\begin{equation} \begin{split} &\int d\theta_1d\theta_2...d\theta_N e^{-\frac{1}{2}\theta_iD_{ij}\theta_j}\\ &=\int d\theta_1d\theta_2...d\theta_N \exp\left\{-\frac{1}{2}\left(\lambda_1\theta_1\theta_2-\lambda_1\theta_2\theta_1+\lambda_2\theta_3\theta_4-\lambda_2\theta_4\theta_3+...+\lambda_m\theta_{m-1}\theta_m-\lambda_m\theta_{2m}\theta_{2m-1}\right)\right\}\\ &=\int d\theta_1d\theta_2...d\theta_N \exp\left\{\lambda_1\theta_2\theta_1+\lambda_2\theta_4\theta_3+...+\lambda_m\theta_{2m}\theta_{2m-1}\right\}\\ &=\int d\theta_1d\theta_2...d\theta_N \exp\left\{\sum_{i=1}^m\lambda_i\theta_{2i}\theta_{2i-1}\right\}\\ &=\int d\theta_1d\theta_2...d\theta_N\prod_{i=1}^m\exp\left\{\lambda_i\theta_{2i}\theta_{2i-1}\right\}\\ &=\int d\theta_1d\theta_2...d\theta_N\prod_{i=1}^m(1+\lambda_i\theta_{2i}\theta_{2i-1})\\ &=\int d\theta_1d\theta_2...d\theta_N\left(\prod_{i=1}^m\lambda_i\right)\theta_2\theta_1\theta_4\theta_3...\theta_N\theta_{N-1}\\ &=\prod_{i=1}^m\lambda_i\\ &=\sqrt{\det(A)} \end{split} \end{equation}

Where we have used that the only the part of the product $(\prod_{i=1}^m(1+\lambda_i\theta_{i+1}\theta_i))$ that survives integration is where we multiply all the grassmann variables (All other terms will vanish because $\int d\theta=0$). At the end of the calculation I used that pairs of grassmann variables commute ([$\theta_2\theta_1,\theta_4\theta_3]=0$)


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.